2013
DOI: 10.1016/j.neuroscience.2012.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in activated corticotropin-releasing factor neurons within stress-related neurocircuitry and hypothalamic–pituitary–adrenocortical axis hormones following restraint in rats

Abstract: Women may be more vulnerable to certain stress-related psychiatric illnesses than men due to differences in hypothalamic-pituitary-adrenocortical (HPA) axis function. To investigate potential sex differences in forebrain regions associated with HPA axis activation in rats, these experiments utilized acute exposure to a psychological stressor. Male and female rats in various stages of the estrous cycle were exposed to 30 min of restraint, producing a robust HPA axis hormonal response in all animals, the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 92 publications
(112 reference statements)
10
80
0
1
Order By: Relevance
“…Our finding that gene transcription in response to acute swim stress shows a more pronounced increase in females than in males is in line with previous reports (Aloisi et al, 1997;Babb et al, 2013). Data in humans also suggest that women are more susceptible to suffer from neuropsychiatric disorders classically associated with stressful experiences, such as post traumatic stress disorder (Breslau, 2009;Tolin and Foa, 2006) or depression (Parker and Brotchie, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that gene transcription in response to acute swim stress shows a more pronounced increase in females than in males is in line with previous reports (Aloisi et al, 1997;Babb et al, 2013). Data in humans also suggest that women are more susceptible to suffer from neuropsychiatric disorders classically associated with stressful experiences, such as post traumatic stress disorder (Breslau, 2009;Tolin and Foa, 2006) or depression (Parker and Brotchie, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…The hippocampus is highly sensitive to stress and plays a critical role in the negative effects of stress on cognitive function and on affective disorders (de Kloet et al, 2005). A few studies have demonstrated that the transcriptional response of the immediate early gene Fos is more pronounced after acute stress in females than males (Aloisi et al, 1997;Babb et al, 2013). However, it remains unknown whether hippocampal gene expression is generally more responsive to acute stress challenges in females than males, or if this effect is restricted to Fos.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that discrepancies could be due to the phase of the estrous cycle as most results failed to find differences (Babb et al, 2013a;Isawaki-Sekino et al, 2009;Viau and Meaney, 1991). Interestingly, there is evidence to suggest that sex differences in ACTH response may be dependent on the particular type of stressor (Babb et al, 2013b;Spinedi et al, 1994), and this is supported by our present results demonstrating greater sex differences in the ACTH response to shock and conditioning than to novel environments. It is of note that brain corticosterone levels appears to be similar in the two sexes despite higher total levels of corticosterone in females (Droste et al, 2009), probably due to the higher levels of corticosteroid-binding globulin in females (i.e.…”
Section: Endocrine Responsesupporting
confidence: 78%
“…Sex-differences in the endocrine response to fear conditioning are important for two main reasons. First, sex differences in ACTH response to stress in rats appear to be dependent on the particular type of stressor studied (Babb et al, 2013b;Spinedi et al, 1994;Watanobe, 2002). Second, characterization of ACTH response to fear-conditioning can contribute to determine whether or not females are actually less sensitive than males to fear conditioning.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Neural outputs from the medial hypothalamic system target regions of the brain associated with defensive responses. These include the periaqueductal grey (PAG), which is a key site for organizing behavioral defensive responses to psychological stressors like predator odor, and the dorsomedial hypothalamus (DMH), which provides massive projections to the paraventricular hypothalamic nucleus (PVN) and integrates the functions of the endocrine defensive response [4]. The PVN constitutes the central part of the hypothalamo-pituitaryadrenal (HPA) axis especially the periventricular and medial parvicellular parts that contain neurons synthesizing hypophysiotropic corticotropin-releasing hormone, which stimulates the secretion of ACTH [8,11].…”
Section: Discussionmentioning
confidence: 99%